Ambipolarity Regulation of Deep‐UV Photocurrent by Controlling Crystalline Phases in Ga2O3 Nanostructure for Switchable Logic Applications. (7th February 2023) - Cheng, Yuexing; Ye, Junhao; Lai, Li; Fang, Shi; Guo, Daoyou
Abstract: Photoelectrochemical photocurrent switching (PEPS) effect can regulate the polarity of photocurrent, which has significant potential applications in areas such as logic gates, photosynapse, and artificial intelligence. In this work, it is reported for the first time that a pure Ga2 O3 photoelectrochemical system exhibits ambipolar photocurrent behavior induced by deep ultraviolet, which is closely linked to the crystalline phase of Ga2 O3 (α or β) and the surface states of oxygen vacancies. Spongy porous nanorod arrays (NRAs) of Ga2 O3 designed here not only increase the contact area of Ga2 O3 with the electrolyte but also can lower largely the reflection of light and improve light‐trapping capacity. For α phase Ga2 O3, the photocurrent is in a forward direction under positive bias and shows a backward direction under negative bias in NaOH solution, exhibiting a distinct ambipolar photocurrent phenomenon, which can be attributed to more oxygen vacancy surface states and lower potential barrier at the semiconductor/electrolyte interface. Furtherly, the effect of the surface states on the ambipolar photocurrent behavior of α‐Ga2 O3 NRAs is demonstrated by various treatment times of oxygen plasma, whose switching point moves from 0 V to −0.19 V with treatment for 30 min and continues to move in the negative direction with the increase of treatment time. Moreover, based on the ambipolar photocurrent behavior of α‐Ga2 O3 NRAs, adjustable Boolean logic gates with voltage are prepared as the input source, offering a new path for the photoelectric device multifunctional integration needed in the Post‐Moore era, with a high accuracy manipulated by solar‐blind deep ultraviolet light. Abstract : The work reports, for the first time, that a pure Ga2 O3 photoelectrochemical system exhibits ambipolar photocurrent behavior induced by deep ultraviolet, which is closely linked to the crystalline phase of Ga2 O3 (α or β). The adjustable logic gates devices based on the ambipolar photocurrent behavior of α‐Ga2 O3 nanorods can offer a new path for the photoelectric device multifunctional integration needed in the post‐Moore era.